The Effects of Cassava Pomace and Protected Soybean Meal on Dairy Milk Production and Quality - Basofi Sabastian; Budi Prasetyo Widyobroto; Andriyani Astuti (Faculty of Animal Science, Universitas Gadjah Mada, 2021)
The objective of the study was to determine the effect of cassava pomace and protected soybean meal on dairy milk production and quality of mid lactating dairy cows. This research was conducted at Turen, Malang from January to April 2020. Twelve lactating Friesian Holstein dairy cows were divided into 2 groups so that each group consisted of 6, namely the control and treatment groups. The feed were a combination of forage and concentrate with a ratio of 35:65 in dry matter (DM). The control group received wet concentrate with DM content of 30.58%, 14.87% CP, and 75.06% TDN, while the treatment groups received concentrate with supplementation of cassava pomace 15% of DM ratio and protected soybean meal 45 g/l milk production. The variables observed were nutrient consumption, milk production and quality. Data between the two groups were analyzed using the Independent Sample T-test. The results showed that the addition of waste cassava and protected soybean meal increased (P<0.05) nutrient consumption (DM, OM, CP, CF, EE, and TDN). Milk production in the treatment group was higher (P<0.05) than control group (9.46 vs. 6.07 Ls/head/day). Milk protein production in the treatment group was higher (P<0.05) than control group (0.37 vs. 0.21 L/head/day). The content of milk protein and milk fat between the control and treatment groups was not significantly different (respectively 3.19 Vs 3.28; 4.46 vs 4.42 %). Milk protein and fat production in the treatment group was higher (P<0.05) than control group (0.21 vs 0.37; and 0.50 vs. 0.30 L/head/day respectively). The composition of glucose and blood urea in control and treatment dairy cows were not significantly different. In conclusion, giving cassava pomace and protected soybean meal to dairy cows during mid lactation increased nutrient consumption, milk production, milk protein production, and milk fat production but did not increase percentage of milk protein and fat. The treatment also did not affect blood glucose and nitrogen urea contents.